Feathers - Woodson, Jacqueline (New York : G.P. Putnam's Sons, 2007)
When a new, white student nicknamed "The Jesus Boy" joins her sixth grade class in the winter of 1971, Frannie's growing friendship with him makes her start to see some things in a new light.
Keywords: Race relations -- Fiction; African Americans -- Fiction; School stories; Deaf -- Fiction; Family life -- Fiction; Religion -- Fiction